Penggunaan laser dalam perawatan gingivektomi (Tinjauan Pustaka) - Marie Louisa; Stephanie Vilit (Jurnal Kedokteran Gigi Terpadu, 2022)
Introduction: Gingival hyperplasia is often treated with gingivectomy. Nowadays, gingivectomy can be done using a laser. This review aims to describe several types of laser used in gingivectomy along with their benefits and disadvantages. Literature review: There are 4 types of laser that can be used in gingivectomy: diode, CO2, Neodymium YAG (Nd:YAG), and erbium: YAG (er:YAG). Laser gingivectomy provides precise cutting, minimal trauma, and good hemostatic property, thus increasing patients comfort. Discussion: Each type of laser has its own benefits and disadvantages. Diode laser provides effective soft tissue cutting and good hemostatic properties along with economical price and size. Conclusion: Laser gingivectomy offers more benefits than conventional gingivectomy. Diode laser can be used effectively for gingivectomy due to its good soft tissue penetration and economical properties